2017
DOI: 10.3390/healthcare5030050
|View full text |Cite
|
Sign up to set email alerts
|

Nurse Perceptions of Artists as Collaborators in Interprofessional Care Teams

Abstract: Increased attention is being given to interprofessional collaboration in healthcare, which has been shown to improve patient satisfaction, patient safety, healthcare processes, and health outcomes. As the arts and artists are being more widely incorporated into healthcare settings throughout the world, professional artists are contributing to interprofessional care teams. A secondary directed content analysis of interviews with 31 nurses on a medical-surgical care unit investigated the roles and impacts of pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 47 publications
0
14
0
Order By: Relevance
“…The intervention was not burdensome or disruptive for HCPs, an issue that can negatively impact clinical care. [48] This feasibility study demonstrated that by placing patients and HCPs at the centre of intervention development, particularly one designed to be intradialytic, can help reduce the impact of the intervention on the adequacy and safety of the patients treatment, and even reduce burden placed on HCPs in the setting.…”
Section: Discussionmentioning
confidence: 87%
“…The intervention was not burdensome or disruptive for HCPs, an issue that can negatively impact clinical care. [48] This feasibility study demonstrated that by placing patients and HCPs at the centre of intervention development, particularly one designed to be intradialytic, can help reduce the impact of the intervention on the adequacy and safety of the patients treatment, and even reduce burden placed on HCPs in the setting.…”
Section: Discussionmentioning
confidence: 87%
“…The intervention was not burdensome or disruptive for HCPs, an issue that can negatively impact clinical care. [9,42] Instead the intervention provided bene ts for both patients and HCPs, potentially by inducing ow states amongst patients, [43] promoting mental wellbeing amongst patients and HCPs [44] and transforming the atmosphere of the clinical environment. [45] Whilst patients did report experiences that would indicate they were experiencing ow states while engaging in the intervention, art appeared to provide a more holistic impact on their wellbeing by improving their self-esteem, providing participants with a sense of purpose, promoting social engagement and generating positive affective states.…”
Section: Discussionmentioning
confidence: 99%
“…The area of nursing presents itself as an outstanding profession for strengthening collaborative interprofessional practice and teamwork through its form of communication with the other components of the health team, promoting harmony, quality in decision making and impacting patients directly with quality care (7)(8) . Teamwork skills such as communication, respect, trust, mutual knowledge, collective power, centralization of actions on the patient, characteristics of the tasks and the environment were practices used during the crisis of the COVID-19 (9) .…”
Section: Collaborative Practices Based On Communication and Professiomentioning
confidence: 99%
“…Therefore, multiprofessional teams unite workers who use specialized knowledge and juxtaposed disciplines, which can culminate in fragility in health care. Otherwise, interprofessional teams are based on problem solving, enhancing effectiveness and quality in care, providing the understanding of collaborative roles and skills for a teamwork (4,(6)(7) .…”
Section: Collaborative Practices Based On Communication and Professiomentioning
confidence: 99%
See 1 more Smart Citation